Perancangan Aplikasi Pemesanan Makanan Berbasis Web di Kantin PT. Pegadaian Kanwil I Medan - Afiksih, Afiksih (Ali Institute of Research and Publication, 2022)
Cafeteria in Pawnshop office regional office 1 medan located behind the main building precisely on the floor 2. This canteen is the only canteen in the office and the place where the staff and employees eat and drink during their hours of rest. Up to the moment of booking in the cafeteria PT.Pegadaian kanwil 1 medan is not computerized. This causes the booking process to be slow. It is not efficient with rest periods are given. Where is the rest time that is given just 1 hour? In this case, the needed application allows buyers in search of food. The food ordering app cafeteria-based website is an application designed to make it easier for buyers and sellers in the book of food and drink. In making the application the authors use the waterfall method, using the programming language PHP, and using MySQL database. The app is designed with a display that is easy to understand, so users can easily use the application. With this application, customers can conduct the process of ordering food without having to queue and is easy to see the food menu, the detail of the food, and the price of food.